Destabilization of counter-propagating Alfvénic instabilities by tangential, co-current neutral beam injection. (29th June 2018) - Podestà, M.; Fredrickson, E.D.; Gorelenkova, M.
Abstract: Injection of high-energy neutrals is a common tool to heat the plasma and drive current non-inductively in fusion devices. Once neutrals ionize, the resulting energetic particles can drive instabilities that are detrimental for the performance and the predictability of plasma discharges. A broad deposition profile of neutrals from neutral beam injection, e.g. by aiming the beam tangentially on the outboard midplane (i.e. off-axis), is often assumed to limit those undesired effects by reducing the radial gradient of the EP density, thus reducing the drive for instabilities. However, this work presents new evidence that tangential neutral beam injection, including off-axis injection near the plasma mid-radius, can also lead to undesired effects such as the destabilization of Alfvénic instabilities. Time-dependent analysis with the TRANSP code indicates that instabilities are driven by a combination of radial and energy gradients in the distribution function of the energetic particles. The mechanisms for wave-particle interaction revealed by the energetic particle phase space resolved analysis are the basis to identify strategies to mitigate or suppress the observed instabilities.